Teratogenic Effects of Arabica Coffee (Coffea arabica L) on Rats During the Organogenesis Period - Reza Destri Anggi; Yuandani; Dalimunthe, Aminah (Indonesian Journal of Pharmaceutical and Clinical Research, 2020)
The purpose of the research was to evaluate the teratogenic effect caused by theprovision of Arabica coffee solution with variations of 0.36 ml, 0.72 ml and 1.08 ml withpositive control of caffeine at a dose of 300 mg / kg bw to rats during organogenesis. Themeasurement parameters in this study are the appearance of reproduction, externalmalformations and scalal malformations. The results in this study found that theadministration of Arabica coffee solution with a volume of 1.08 ml and caffeine 300 mg /kg bb caused an abnormality in the reproductive appearance of weight loss and body length,whereas for extrenal malformation and scalal malforation no abnormalities were found ineach administration of the solution Arabica coffee and caffeine. Â